Light hydrocarbon aromatization catalyst capable of increasing yield of light alkane, preparation method and application of light hydrocarbon aromatization catalyst

By using a combined catalyst of hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve and active metal, the problems of light hydrocarbon aromatization catalysts are easily deactivated and have strong acidity, and the effect of efficient conversion of low-carbon alkanes and reducing dry gas yield is achieved.

CN119897158AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311401033.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The existing light hydrocarbon aromatization catalysts are prone to carbon accumulation and inactivation under reaction conditions, and the strong acidity causes the light hydrocarbon raw materials to be easily cracked into low-value dry gas, making it difficult to achieve high conversion and high selectivity.

Method used

A hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve is used as an active component, combining active metals and binders, and a catalyst with high carbon capacity and moderate acidity is formed through specific preparation methods and process conditions.

Benefits of technology

The yield of low-carbon alkanes is significantly improved, the yield of dry gas is reduced, the single-pass reaction period of the catalyst is extended, the amount of carbon deposit is reduced, and the stability and regeneration performance of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004515270730000181
    Figure BDA0004515270730000181
  • Figure BDA0004515270730000191
    Figure BDA0004515270730000191
  • Figure BDA0004515270730000192
    Figure BDA0004515270730000192
Patent Text Reader

Abstract

A light hydrocarbon aromatization catalyst capable of increasing the yield of light alkane comprises a hydrogen type Silicalite-1 (at) ZSM-5 core-shell molecular sieve, an active metal and / or a binder, the hydrogen type Silicalite-1 (at) ZSM-5 core-shell molecular sieve takes a Silicalite-1 molecular sieve as a core layer and a ZSM-5 molecular sieve as a shell layer, and the particle size of the hydrogen type Silicalite-1 (at) ZSM-5 core-shell molecular sieve is 90-140 nm. The catalyst is applied to light hydrocarbon aromatization reaction, has higher low-carbon alkane yield and lower dry gas yield, and is good in stability, long in one-way reaction period and low in carbon deposit amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst, a preparation method and an application thereof, and in particular to a light hydrocarbon aromatization catalyst capable of producing more low-carbon alkanes, a preparation method and an application thereof in the reaction of converting light hydrocarbons into propane, butane and aromatics. Background Art

[0002] With the annual increase in my country's oil refining capacity, a large amount of light hydrocarbon components such as liquefied petroleum gas, reforming top oil and aromatic raffinate produced by refineries have not been reasonably utilized. How to convert this part of low-value light hydrocarbon resources into high-value chemical raw materials such as low-carbon alkanes and light aromatics BTX is an urgent problem to be solved in the current transformation of oil refining to chemical industry. Light hydrocarbon aromatization technology is a light hydrocarbon resource efficient utilization technology that converts light hydrocarbon raw materials into high-value light aromatics and propane through a series of parallel reactions such as cracking, dehydrogenation, disproportionation, hydrogen transfer, cyclization, isomerization, etc. under the action of catalysts at low reaction temperatures. Among them, the research on light hydrocarbon aromatization catalysts has also experienced a transformation from metal-supported catalysts to molecular sieve catalysts. For light hydrocarbon aromatization technology, the development of new catalysts with high conversion rate, high selectivity and high stability is a current research hotspot.

[0003] CN112588314A discloses the preparation and application of a catalyst for producing propane by converting light hydrocarbons. The catalyst uses one or more of HZSM-5 molecular sieve, HY type molecular sieve and β molecular sieve, mordenite and SAPO-34 molecular sieve as active components, and uses one or more of rare earth metals, Zn, Ga, Ni, Ag, Mo, Cu, P and the like as modifying elements. The preparation method comprises the following steps: firstly adding a binder to the active component of the molecular sieve, kneading, extruding, drying and calcining, then modifying the active component with one or more of Zn, Ga, Ni, Ag, Mo, Cu and P as modifying elements, drying and calcining, and finally aging with water vapor to obtain the catalyst for producing propane by converting light hydrocarbons; and finally aging the catalyst at a reaction temperature of 320-450°C, a reaction pressure of 0.1-3.0 MPa and a space velocity of 0.1-2.0 h -1 Under the conditions of , light hydrocarbons are introduced into contact with the catalyst for reaction, and a better propane yield can be obtained.

[0004] CN110951500A discloses a method for producing propane and gasoline from paraffins, comprising subjecting the hydrocarbons to a non-hydrogenated state, at 0.1-3.0 MPa, 400-550°C, and a feed mass space velocity of 0.1-10.0 h -1The hydrocarbon conversion catalyst comprises 20-85 mass % of ZSM series zeolite and 15-80 mass % of binder, the ZSM series zeolite is ZSM-5 and / or ZSM-35, the α value of the catalyst is 60-80, and the paraffin is selected from one or more of C5-C12 paraffins. The method can produce propane under non-hydrogenation conditions and produce high-octane gasoline blending components as a by-product.

[0005] CN113385215A discloses a preparation method and application of a catalyst for hydrogen reforming to produce propane, wherein the catalyst uses a micron-sized SAPO-34 molecular sieve as a crystal core and a ZSM-5 molecular sieve as an outer layer, and a SAPO-34 / ZSM-5 composite molecular sieve catalyst with a core-shell structure is prepared. At the same time, the composite molecular sieve pore structure and acid distribution are modified by a modification method, and the catalyst can catalytically crack light hydrocarbons to produce propane under hydrogen conditions.

[0006] The above-mentioned process routes for preparing low-carbon alkanes, light aromatics and gasoline using light hydrocarbons as raw materials are all light hydrocarbon aromatization technology routes. Current application research is mostly focused on the process stage of fixed-bed catalysts, which have the problem of catalysts being easily deactivated by carbon deposition and requiring frequent switching and regeneration. It is urgent to develop new catalysts with moderate acidity, strong carbon capacity, high activity and high stability. Summary of the invention

[0007] In view of the problems that the catalysts currently using the light hydrocarbon aromatization mechanism to convert light hydrocarbons into low-carbon alkanes are prone to coking and deactivation and are difficult to regenerate, and the light hydrocarbon raw materials are easily cracked into low-value dry gas due to the strong acidity of the catalyst, the present invention provides a light hydrocarbon aromatization catalyst for producing more low-carbon alkanes, a preparation method and application thereof. The catalyst is used for the light hydrocarbon aromatization reaction, has a higher low-carbon alkane yield and a lower dry gas yield, and the catalyst has good stability, a long single-pass reaction cycle and a low carbon deposition amount.

[0008] The first aspect of the present invention provides a light hydrocarbon aromatization catalyst for producing more low-carbon alkanes, comprising a hydrogenated Silicalite-1@ZSM-5 core-shell molecular sieve, an active metal and / or a binder. The hydrogenated Silicalite-1@ZSM-5 core-shell molecular sieve has a Silicalite-1 molecular sieve as a core layer and a ZSM-5 molecular sieve as a shell layer, and has a particle size of 90 to 140 nm.

[0009] The second aspect of the present invention provides a method for preparing the catalyst described in the first aspect of the present invention. When the catalyst includes a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve and an active metal, the preparation method includes: impregnating the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve with a solution of a compound containing an active metal under alkaline conditions, and then performing a first drying and a first calcination step ST1; when the catalyst includes a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, an active metal and a binder, further mixing the product obtained in the step ST1 and a binder precursor to form a mixture, and then performing a second drying and a second calcination step ST2.

[0010] The catalyst of the invention uses hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve as an active component and is used for light hydrocarbon aromatization reaction, has a higher low-carbon alkane yield and a lower dry gas yield, and has good catalyst stability, a long single-pass reaction cycle, and a low carbon deposition amount.

[0011] The catalyst of the present invention can effectively reduce the carbon deposition and deactivation phenomenon of the catalyst under aromatization reaction conditions. The active component hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve has a higher carbon holding capacity, and the weaker acidity of the molecular sieve in the core layer reduces the carbon deposition in the core layer, so that the carbon species are mostly enriched in the shell layer, and the catalyst is easy to regenerate. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The X-ray diffraction spectrum of the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve S1 prepared in Example 1;

[0013] Figure 2 This is a scanning electron microscope photo of the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve S1 prepared in Example 1;

[0014] Figure 3 This is a transmission electron microscope photo of the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve S1 prepared in Example 1;

[0015] Figure 4 This is an enlarged transmission electron microscope photo of the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve S1 prepared in Example 1;

[0016] Figure 5 This is a transmission electron microscope photograph of S1' after the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve prepared in Example 1 was loaded with metal. DETAILED DESCRIPTION

[0017] The catalyst of the present invention uses hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve as an active component, and is suitable for C5-C10 chain alkanes, or light hydrocarbons and naphtha raw materials with them as the main components to undergo conversion reactions under non-hydrogen conditions. The reactants undergo a series of parallel reactions such as cracking, dehydrogenation, hydrogen transfer and aromatization under the action of the catalyst to generate propane, butane and high-value light aromatic hydrocarbons. The hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve uses Silicalite-1 molecular sieve as a core layer and ZSM-5 molecular sieve as a shell layer. The epitaxial growth of ZSM-5 molecular sieve on the Silicalite-1 molecular sieve can effectively solve the problem of blockage inside the molecular sieve pores and difficulty in product desorption. Using Silicalite-1 as a core layer can reduce the B acid content inside the core-shell molecular sieve, thereby inhibiting the strong cracking reaction of the reactants inside the molecular sieve, and making the cracking reaction occur on the ZSM-5 molecular sieve in the shell layer, thereby reducing the yield of dry gas and the amount of carbon deposits on the molecular sieve as a whole.

[0018] The catalyst of the present invention can make the chain alkane with carbon number of 5 to 10 generate propane, butane and light aromatic hydrocarbons with low carbon number under wide reaction conditions, wherein the yield of propane is greater than 60%, and the yield of butane is greater than 14%.

[0019] The catalyst of the present invention comprises a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, an active metal and / or a binder, wherein the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve has a Silicalite-1 molecular sieve as a core layer and a ZSM-5 molecular sieve as a shell layer, and has a particle size of 90 to 140 nm. The Silicalite-1@ZSM-5 core-shell molecular sieve used in the catalyst of the present invention has a small particle size, which can significantly enhance the activity and stability of the catalyst and reduce the amount of carbon deposits on the catalyst.

[0020] The catalyst of the present invention, the active metal is a Group VIII metal, preferably one of cobalt, nickel and iron, the content of the active metal is 0-10.0% by mass, preferably 0-6.0% by mass, calculated based on the mass of the molecular sieve, the active metal component as a dehydrogenation functional component, has a dehydrogenation function in the reaction, is conducive to the aromatization reaction, on the other hand, the core-shell molecular sieve after loading the metal can have a higher carbon holding capacity; the binder is silicon oxide or aluminum oxide, the content of the binder is 0-45% by mass, calculated based on the total mass of the hydrogenated Silicalite-1@ZSM-5 core-shell molecular sieve and the binder.

[0021] The catalyst of the present invention has a SiO2 / Al2O3 molar ratio of 20 to 200, preferably 40 to 80. The ZSM-5 molecular sieve as the shell has a suitable silicon-aluminum ratio, provides a more suitable amount of acid, and causes the chain alkane to undergo cracking reaction at its acidic site to increase the production of small molecular chain alkanes such as propane and butane.

[0022] The catalyst of the present invention has a total specific surface area of ​​200 to 420 m 2 / g, preferably 240-280m 2 / g, total pore volume is 0.30~0.70cm 3 / g, preferably 0.40-0.50cm 3 / g; Preferably, when the catalyst of the present invention does not contain a binder, the micropore specific surface area is 330 to 370 m 2 / g, micropore volume is 0.10~0.20cm 3 / g, preferably 0.14 to 0.19 cm 3 / g.

[0023] The catalyst of the present invention, the aluminum oxide is preferably γ-Al2O3. The catalyst can be in the shape of bars, pellets, particles or microspheres, so as to be suitable for reactions in fixed bed, moving bed or fluidized bed reactors.

[0024] The catalyst of the present invention comprises a Silicalite-1@ZSM-5 core-shell molecular sieve with a Silicalite-1 molecular sieve as a core layer and a ZSM-5 molecular sieve as a shell layer, and a particle size of 90 to 140 nm, preferably 100 to 130 nm; the particle size of the Silicalite-1 molecular sieve is 40 to 80 nm, preferably 50 to 70 nm, and the thickness of the ZSM-5 shell layer is 30 to 70 nm, preferably 45 to 60 nm; the silicon-aluminum ratio of the ZSM-5 molecular sieve is 20 to 200, preferably 40 to 80; the total specific surface area of ​​the Silicalite-1@ZSM-5 core-shell molecular sieve is 300 to 470 m 2 / g, preferably 420-450m 2 / g, micropore specific surface area is 260~390m 2 / g, preferably 350 to 380 m 2 / g, total pore volume is 0.20~0.60cm 3 / g, preferably 0.30 to 0.55 cm 3 / g, micropore volume is 0.10~0.30cm 3 / g, preferably 0.16 to 0.28 cm 3 / g.

[0025] The catalyst of the present invention, the Silicalite-1@ZSM-5 core-shell molecular sieve is obtained by a preparation method comprising the following steps:

[0026] (1) mixing a template, a first silicon source and water to obtain a core layer molecular sieve synthesis system, and performing aging I and crystallization I to obtain an intermediate product;

[0027] (2) The intermediate product obtained in step (1), an aluminum source, a second silicon source, an alkali source, an anion-cation balance agent and water are mixed to obtain a shell molecular sieve synthesis system, and after aging II and crystallization II, the obtained solid is washed, dried and calcined to obtain the Sililcalite-1@ZSM-5 core-shell molecular sieve.

[0028] (3) subjecting the Silicalite-1@ZSM-5 core-shell molecular sieve obtained in step (2) to ion exchange in a solution containing ammonium ions, and washing and calcining again to obtain the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve.

[0029] Preferably, a hydrolysis promoter may be added to the core layer molecular sieve synthesis system described in step (1), wherein the hydrolysis promoter is an alcohol and / or a weak base, more preferably at least one of ethylene glycol, methanol, ethanol, and ammonia water; the first silicon source is calculated as SiO2, the mass ratio of the first silicon source to the hydrolysis promoter is 1 to 5, the mass ratio of the first silicon source to the template is 0.1 to 5, and the mass ratio of the first silicon source to water is 1 to 10. Optionally, the upper limit of the mass ratio of the first silicon source to the hydrolysis promoter is independently selected from 5.0, 4.0, 3.0, and 2.0, and the lower limit is independently selected from 1.0, 4.0, 3.0, and 2.0. Optionally, the upper limit of the mass ratio of the first silicon source to the template is independently selected from 1.2, 1, 0.8, 0.6, and 0.5, and the lower limit is independently selected from 1, 0.8, 0.6, 0.5, and 0.1.

[0030] Preferably, in step (1), after crystallization I, a step of recovering the template by distillation or centrifugation is included. When the template is recovered by distillation, the temperature is 60 to 120° C., preferably 80 to 100° C., and the distillation time is 0.5 to 6 hours, preferably 2 to 4 hours.

[0031] Preferably, in step (2), the anion-cation balance agent is one of a strong acid-weak base salt, a strong base-weak acid salt, a strong acid-strong base salt or a weak acid-weak base salt, more preferably at least one of sodium acetate, sodium chloride, ammonium acetate and ammonium chloride.

[0032] Preferably, the first silicon source and the second silicon source are independently selected from at least one of tetraethyl silicate, silica sol, water glass, white carbon black, and silica gel powder; the aluminum source is at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, and aluminum chloride; the alkali source is at least one of sodium hydroxide, potassium hydroxide, and ammonia water; and the template is at least one of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, n-butylamine, tetrapropylammonium bromide, and 1,6-hexanediamine.

[0033] Preferably, in step (2), the second silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the molar ratio of the second silicon source to the aluminum source is 20 to 200. Optionally, the upper limit of the molar ratio of the second silicon source to the aluminum source is independently selected from 200, 170, 100, 80, 50, and the lower limit is independently selected from 40, 170, 100, 80, 50.

[0034] Preferably, in step (2), the aluminum source is calculated as Al2O3, the alkali source is calculated as NaOH, and the mass ratio of the intermediate product: aluminum source: alkali source: anion and cation balance agent: water is (50-300): 1: (1-10): (1-30): (50-200).

[0035] Preferably, the aging I has a temperature of 10-50°C, preferably 25-35°C, and a time of 0.5-12h, preferably 4-6h; the crystallization I has a temperature of 80-250°C, preferably 100-150°C, and a time of 18-72h, preferably 24-48h; the aging II has a temperature of 10-50°C, preferably 25-35°C, and a time of 0.5-12h, preferably 4-6h; the crystallization II has a temperature of 80-250°C, preferably 150-200°C, and a time of 18-72h, preferably 24-48h.

[0036] Optionally, the upper limit of the temperature of the crystallization I is independently selected from 150°C, 140°C, 130°C, 120°C, and the lower limit is independently selected from 100°C, 140°C, 130°C, 120°C. The upper limit of the time of the crystallization I is independently selected from 48h, 36h, 24h, and the lower limit is independently selected from 12h, 36h, 24h. Optionally, the upper limit of the temperature of the crystallization II is independently selected from 200°C, 180°C, 160°C, 140°C, 120°C, and the lower limit is independently selected from 100°C, 180°C, 160°C, 140°C, 120°C. The upper limit of the time of the crystallization II is independently selected from 36h, 24h, 12h, and the lower limit is independently selected from 6h, 12h, 24h.

[0037] The ion exchange and the washing, drying and calcining after the ion exchange are conventional operations in the art and will not be described in detail here.

[0038] When the catalyst of the present invention comprises hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve and a binder, the preparation method thereof is a conventional molding method in the art.

[0039] 30. When the catalyst of the present invention comprises hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve and active metal, its preparation method comprises: impregnating the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve with a solution of a compound containing active metal under alkaline conditions, and then performing a first drying and a first calcination step ST1; when the catalyst comprises hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, active metal and a binder, further mixing the product obtained in the step ST1, a binder precursor and a peptizing agent to form a mixture, and then performing a second drying and a second calcination step ST2. Wherein, the amount of the solution of the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve and the active metal compound in the impregnation is 0.1-10 g / ml, the alkaline condition is pH 8-12, preferably pH 8-10, and the pH value of the impregnation solution can be adjusted with ammonia water; the impregnation temperature is 30-100°C, preferably 45-75°C; the active metal-containing compound is a soluble Group VIII metal salt, preferably a nitrate or chloride of a Group VIII metal; the soluble Group VIII metal salt is one of a soluble cobalt salt, a soluble nickel salt and a soluble iron salt, the soluble cobalt salt is selected from cobalt nitrate hexahydrate and cobalt chloride; the soluble nickel salt is selected from nickel nitrate hexahydrate, nickel chloride, and nickel sulfate; the soluble iron salt is selected from ferric chloride, ferric nitrate, and ferric sulfate; the peptizing agent is nitric acid and / or an organic acid, and the acid concentration in the peptizing agent is 0.1-5 wt%, preferably 10 wt%. The selected concentration is 0.5-2wt%, and the amount of the peptizing agent relative to the product obtained in step ST1 is 0.01-0.1ml / g; the binder precursor is pseudo-boehmite powder or silica gel powder, and the amount of the binder precursor makes the catalyst binder content 0-45% by mass, calculated based on the total mass of the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve and the binder; the first drying and second drying temperatures are independently 50-200°C, preferably 80-120°C, the first drying and second drying times are independently 2-8h, and the preferred drying time is 4-6h; the first calcination and second calcination temperatures are independently 400-700°C, preferably 450-650°C, and more preferably 500-600°C, the first calcination and second calcination times are independently 4-12h, and the preferred calcination time is 6-8h.

[0040] The light hydrocarbon aromatization reaction method for producing more low-carbon alkanes provided by the present invention comprises contacting and reacting a raw material containing light hydrocarbons with a catalyst in the presence of an inert gas and under aromatization reaction conditions, wherein the catalyst is the catalyst provided by the present invention.

[0041] The present invention provides a light hydrocarbon aromatization reaction method for producing more low-carbon alkanes. The aromatization reaction conditions are: temperature 380-450°C, pressure 0.1-1Mpa, feed mass space velocity 0.1-5h -1 , the volume ratio of inert gas and light hydrocarbon is 500-2000:1.

[0042] The present invention provides a light hydrocarbon aromatization reaction method for producing more low-carbon alkanes, wherein the light hydrocarbon is a C5-C10 chain alkane, preferably a C5-C7 chain alkane; the light hydrocarbon can be one of the C5-C10 chain alkanes, such as n-hexane or n-heptane, or a mixture of chain alkanes with different structures of the same carbon number in the C5-C10 chain alkanes, such as a mixture of C6 chain alkanes, or a mixture of chain alkanes with several carbon numbers, such as a mixture of C5-C7 chain alkanes. The C5-C10 chain alkanes can be a mixture of pure chain alkanes with different carbon numbers or an industrial raw material of light hydrocarbon naphtha containing impurities within the same carbon number range, such as liquefied petroleum gas, reforming top oil and aromatic raffinate oil.

[0043] The present invention provides a light hydrocarbon aromatization reaction method for producing more low-carbon alkanes. In the light hydrocarbon-containing raw material, preferably the C5-C10 alkane content is 30-70% by mass, the olefin content is 10-30% by mass, and the aromatic content is 10-20% by mass. More preferably, the C5-C10 alkane content is 30-50% by mass, the C6 alkane content is 20-30% by mass, and the C7 alkane content is 10-20% by mass.

[0044] After the catalyst of the present invention is deactivated, it can be regenerated and reused. The catalyst regeneration method is: treating the catalyst with an oxygen-containing inert gas, the oxygen content in the inert gas is 0.5-20% by volume, the inert gas is preferably nitrogen, the regeneration temperature is 400-550°C, the pressure is 0.1-3MPa, and the gas / agent volume ratio is 250-1000.

[0045] The light hydrocarbon aromatization reaction device for producing more low-carbon alkanes according to the present invention can adopt fixed bed, moving bed, fluidized bed and other types of devices, and the reaction raw materials do not need to be refined. Preferably, a fixed bed reactor is used for the reaction.

[0046] The raw materials and reagents in the examples of the present invention were purchased from commercial sources.

[0047] The analysis method involved in the present invention is as follows: using XRDWUX70 analysis method to perform X-ray diffraction pattern analysis, using PABETALL analysis method to perform nitrogen adsorption and desorption analysis, and using SEMMORPHO analysis method to perform SEM morphology analysis.

[0048] The present invention is further described in detail below by examples, but the present invention is not limited thereto.

[0049] Examples 1 to 8 are preparation examples of the catalyst of the present invention, and test examples 1 to 3 are catalytic reaction performance examples.

[0050] Comparative Example 1 is an example of preparing a non-core-shell molecular sieve catalyst, and Comparative Example 2 is an example of preparing a catalyst using a method in which the Silicalite-1@ZSM-5 core-shell molecular sieve is first formed and then loaded with active metals.

[0051] Example 1

[0052] (I) Preparation of hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve:

[0053] Step (1): under stirring conditions, tetraethyl silicate, tetrapropylammonium hydroxide, ethanol and deionized water are added into a reaction kettle to obtain a core layer molecular sieve synthesis system, wherein the mass ratio of tetraethyl silicate (in terms of SiO2) to tetrapropylammonium hydroxide is 1.1, the mass ratio of tetraethyl silicate (in terms of SiO2) to ethanol is 4.6, and the mass ratio of tetraethyl silicate (in terms of SiO2) to water is 1.8; after stirring evenly, aging at 35°C for 6h, the mixture is transferred into a crystallization kettle and crystallized at 120°C for 48h; the crystallization reaction product is separated by centrifugation to obtain a recovered template and an intermediate product;

[0054] Step (2): adding sodium aluminate, silica sol, sodium chloride, sodium hydroxide and deionized water to the intermediate product to obtain a shell molecular sieve synthesis system, wherein the mass ratio of the intermediate product: sodium aluminate (calculated as Al2O3): NaOH: sodium chloride: water is 108.3:1:4.17:4.1:118.3, and the molar ratio of silica sol (calculated as SiO2): sodium aluminate (calculated as Al2O3) is 40. After stirring evenly, aging at 50°C for 6h, the mixture is transferred to a crystallization kettle and crystallized at 150°C for 24h. The obtained solid is washed, dried and calcined to obtain the Silicalite-1@ZSM-5 core-shell molecular sieve.

[0055] Step (3): Take 100 g of the Silicalite-1@ZSM-5 core-shell molecular sieve obtained in step (2), perform ion exchange in 500 ml of 1 mol / L ammonium chloride solution, wash again, dry, and calcine to obtain a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, denoted as S1.

[0056] Figure 1 is the powder X-ray diffraction spectrum of S1, which has an obvious MFI topological structure; Figure 2 This is a scanning electron microscope photo of S1, which has a regular morphology; Figure 3 This is a transmission electron microscope photo of S1, which shows that S1 has an obvious core-shell structure; Figure 4 This is an enlarged transmission electron microscope photo of S1, which shows that it has a distinct core-shell structure, with the core layer particle size of 40-60nm and the outer edge of the shell layer of 20-40nm.

[0057] (ii) Loading active metals:

[0058] 100 g of H-type Silicalite-1@ZSM-5 core-shell molecular sieve S1 was taken and impregnated with 300 ml of a hexahydrated cobalt nitrate aqueous solution with a concentration of 0.01 g / ml and a pH value of 8.5 at 80°C for 2 hours. The impregnated solid was first dried at 100°C for 4 hours, and then transferred to a muffle furnace for a first calcination at 550°C for 6 hours to obtain a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve S1' loaded with active metals.

[0059] Figure 5 This is a transmission electron microscope photograph of S1', from which it can be seen that the active metal loading of the catalyst prepared by the present invention is uniform.

[0060] (III) Molding:

[0061] Take 62g of S1' and 38g of pseudo-boehmite powder (produced by Sasol, Germany, with an alumina content of 75% by mass, the same below) and mix them evenly, add 50g of a 1.0% by mass nitric acid aqueous solution, knead and shape them, and extrude them into particles with a diameter of 2mm and a length of 2-3mm using an extruder. After the second drying is carried out in an oven at 100°C for 2h, the particles are transferred to a muffle furnace at 550°C for a second calcination for 6h to obtain the catalyst C1.

[0062] Table 1 shows the characterization results of the structural properties of S1, S1' and C1, and Table 2 shows the composition of catalyst C1.

[0063] Example 2

[0064] (I) Preparation of hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve:

[0065] Step (1): under stirring conditions, tetraethyl silicate, n-butylamine, ethanol and deionized water are added to a reaction kettle to obtain a core layer molecular sieve synthesis system, wherein the mass ratio of tetraethyl silicate (in terms of SiO2) to n-butylamine is 2.3, the mass ratio of tetraethyl silicate (in terms of SiO2) to ethanol is 3.5, and the mass ratio of tetraethyl silicate (in terms of SiO2) to water is 5.0; after stirring evenly, the mixture is aged at 35°C for 3 hours and then transferred to a crystallization kettle for crystallization at 100°C for 48 hours; the crystallization reaction product is separated by distillation to obtain a recovered template and an intermediate product; the distillation conditions are: the intermediate product slurry is taken into a rotary evaporator, the temperature is increased to 80°C at 2°C per minute under room temperature, and rotary evaporated at 80°C for 4 hours, and the rotation frequency of the rotary evaporator is 15 rpm;

[0066] Step (2): adding aluminum sulfate, white carbon black, sodium chloride, sodium hydroxide and deionized water to the intermediate product to obtain a shell molecular sieve synthesis system, wherein the mass ratio of the intermediate product: aluminum sulfate (calculated as Al2O3): NaOH: sodium chloride: water is 216.7:1:8.31:8.37:328.9, and the molar ratio of white carbon black (calculated as SiO2): aluminum sulfate (calculated as Al2O3) is 80. After stirring evenly, aging at 35°C for 3h, the mixture is transferred to a crystallization kettle and crystallized at 150°C for 36h. The obtained solid is washed, dried and calcined to obtain the Silicalite-1@ZSM-5 core-shell molecular sieve.

[0067] Step (3): Take 100 g of the Silicalite-1@ZSM-5 core-shell molecular sieve obtained in step (2), perform ion exchange in 500 ml of 1 mol / L ammonium chloride solution, wash again, dry, and calcine to obtain a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, denoted as S2.

[0068] (ii) Loading active metals:

[0069] 100 g of H-type Silicalite-1@ZSM-5 core-shell molecular sieve S2 was impregnated with 500 ml of a 0.01 g / ml, pH 8.5, hexahydrated cobalt nitrate aqueous solution at 80°C for 2 hours, the impregnated solid was dried at 80°C for 6 hours, and then transferred to a muffle furnace and calcined at 600°C for 4 hours to obtain catalyst C2. Table 1 shows the structural property characterization results of S2 and C2, and Table 2 shows the composition of catalyst C2.

[0070] Example 3

[0071] (I) Preparation of hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve:

[0072] Step (1): adding tetraethyl silicate, tetrapropylammonium hydroxide, methanol and deionized water into a reaction kettle under stirring conditions to obtain a core layer molecular sieve synthesis system, wherein the mass ratio of tetraethyl silicate (calculated as SiO2) to tetrapropylammonium hydroxide is 3.0, the mass ratio of tetraethyl silicate (calculated as SiO2) to methanol is 2.5, and the mass ratio of tetraethyl silicate (calculated as SiO2) to water is 3.5; after stirring evenly, aging at 35°C for 3h, transferring to a crystallization kettle, and crystallizing at 100°C for 24h; centrifuging and separating the crystallization reaction product to obtain a recovered template and an intermediate product;

[0073] Step (2): adding aluminum sulfate, water glass, ammonium acetate, sodium hydroxide and deionized water to the intermediate product to obtain a shell molecular sieve synthesis system, wherein the mass ratio of the intermediate product: aluminum sulfate (calculated as Al2O3): NaOH: ammonium acetate: water is 216.45:1:8.2:14.36:322.21, and the molar ratio of water glass (calculated as SiO2): aluminum sulfate (calculated as Al2O3) is 150. After stirring evenly, aging at 35°C for 3h, the mixture is transferred to a crystallization kettle and crystallized at 150°C for 48h. The obtained solid is washed, dried and calcined to obtain the Silicalite-1@ZSM-5 core-shell molecular sieve.

[0074] Step (3): Take 100 g of the Silicalite-1@ZSM-5 core-shell molecular sieve obtained in step (2), perform ion exchange in 500 ml of 1 mol / L ammonium chloride solution, wash again, dry, and calcine to obtain a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, denoted as S3.

[0075] (ii) Molding:

[0076] Take 85g S3 and 16.7g silica gel powder (silicon oxide content is 90% by mass), mix them evenly, add 50g 1.0% by mass nitric acid aqueous solution, knead them into shape, and extrude them into particles with a diameter of 2mm and a length of 2-3mm using an extruder. After drying in an oven at 100°C for 4h, transfer them to a muffle furnace at 550°C and roast them for 6h to obtain the catalyst C3.

[0077] Table 1 shows the structural property characterization results of S3 and C3, and Table 2 shows the composition of catalyst C3.

[0078] Example 4

[0079] (I) Preparation of hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve:

[0080] Step (1): under stirring conditions, tetraethyl silicate, tetrapropylammonium hydroxide, methanol and deionized water are added into a reaction kettle to obtain a core layer molecular sieve synthesis system, wherein the mass ratio of tetraethyl silicate (in terms of SiO2) to tetrapropylammonium hydroxide is 1.5, the mass ratio of tetraethyl silicate (in terms of SiO2) to methanol is 4.8, and the mass ratio of tetraethyl silicate (in terms of SiO2) to water is 2.5; after stirring evenly, aging at 50°C for 3h, the mixture is transferred into a crystallization kettle and crystallized at 150°C for 24h; the crystallization reaction product is separated by centrifugation to obtain a recovered template and an intermediate product;

[0081] Step (2): adding aluminum chloride, silica sol, sodium chloride, sodium hydroxide, and deionized water to the intermediate product to obtain a shell molecular sieve synthesis system, wherein the mass ratio of the intermediate product: Al2O3: NaOH: sodium chloride: water is 215.8:1:8.73:9.86:322.04, and the molar ratio of silica sol (in terms of SiO2): Al2O3 is 40. After stirring evenly, aging at 50°C for 3h, the mixture is transferred to a crystallization kettle and crystallized at 160°C for 24h. The obtained solid is washed, dried, and calcined to obtain Silicalite-1@ZSM-5 core-shell molecular sieve.

[0082] Step (3): Take 100 g of the Silicalite-1@ZSM-5 core-shell molecular sieve obtained in step (2), perform ion exchange in 500 ml of 1 mol / L ammonium chloride solution, wash again, dry, and calcine to obtain a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, denoted as S4.

[0083] (ii) Loading active metals:

[0084] Take 100 grams of H-type Silicalite-1@ZSM-5 core-shell molecular sieve S4, impregnate it with 500 ml of nickel nitrate hexahydrate aqueous solution with a concentration of 0.01 g / ml and a pH value of 8.5 at 80°C for 2 hours, dry the impregnated solid at 100°C for 4 hours, and then transfer it to a muffle furnace for a first calcination at 550°C for 6 hours to obtain hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve S4' loaded with active metals.

[0085] (III) Molding:

[0086] Take 65g S4' and 35g pseudo-boehmite powder (produced by Sasol, Germany, with an alumina content of 75% by mass, the same below) and mix them evenly, add 50g of a 1.0% by mass nitric acid aqueous solution, knead and shape them, and extrude them into particles with a diameter of 2mm and a length of 2-3mm using an extruder. Perform a second drying at 100°C in an oven for 6h, and then transfer them to a muffle furnace at 650°C for a second calcination for 5h to obtain the catalyst C4.

[0087] Table 1 shows the characterization results of the structural properties of S4, S4' and C4, and Table 2 shows the composition of catalyst C4.

[0088] Example 5

[0089] (I) Preparation of hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve:

[0090] Step (1): adding tetraethyl silicate, 1,6-hexanediamine, ethanol and deionized water into a reaction kettle under stirring conditions to obtain a core layer molecular sieve synthesis system, wherein the mass ratio of tetraethyl silicate (in terms of SiO2) to 1,6-hexanediamine is 0.8, the mass ratio of tetraethyl silicate (in terms of SiO2) to ethanol is 4.2, and the mass ratio of tetraethyl silicate (in terms of SiO2) to water is 6.5; stirring evenly, aging at 35°C for 3h, and then transferring to a crystallization kettle for crystallization at 150°C for 24h; centrifuging and separating the crystallization reaction product to obtain a recovered template and an intermediate product;

[0091] Step (2): adding aluminum sulfate, water glass, ammonium acetate, sodium hydroxide and deionized water to the intermediate product to obtain a shell molecular sieve synthesis system, wherein the mass ratio of the intermediate product: aluminum sulfate (calculated as Al2O3): NaOH: ammonium acetate: water is 209.95:1:7.49:21.64:329.46, and the molar ratio of water glass (calculated as SiO2): aluminum sulfate (calculated as Al2O3) is 40. After stirring evenly, aging at 35°C for 3h, the mixture is transferred to a crystallization kettle and crystallized at 180°C for 24h. The obtained solid is washed, dried and calcined to obtain Silicalite-1@ZSM-5 core-shell molecular sieve.

[0092] Step (3): Take 100 g of the Silicalite-1@ZSM-5 core-shell molecular sieve obtained in step (2), perform ion exchange in 500 ml of 1 mol / L ammonium chloride solution, wash again, dry, and calcine to obtain a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, denoted as S5.

[0093] (ii) Loading active metals:

[0094] Take 100 grams of H-type Silicalite-1@ZSM-5 core-shell molecular sieve S5, impregnate it with 300 ml of ferric chloride aqueous solution with a concentration of 0.01 g / ml and a pH value of 8.5 at 80°C for 2 hours, dry the impregnated solid at 100°C for 4 hours, and then transfer it to a muffle furnace for a first calcination at 550°C for 6 hours to obtain hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve S5' loaded with active metals.

[0095] (III) Molding:

[0096] Take 70g S5' and 33.4g silica gel powder (silicon oxide content is 90% by mass), mix them evenly, add 50g 1.0% by mass nitric acid aqueous solution, knead them into shapes, extrude them into particles with a diameter of 2mm and a length of 2-3mm using an extruder, carry out a second drying at 100°C in an oven for 5h, and then transfer them to a muffle furnace at 550°C for a second calcination for 6h to obtain the catalyst C5.

[0097] Table 1 shows the structural property characterization results of S5, S5' and C5, and Table 2 shows the composition of catalyst C5.

[0098] Example 6

[0099] (I) Preparation of hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve:

[0100] Silicalite-1@ZSM-5 core-shell molecular sieve was prepared according to the method of Example 1, except that ethanol was not added in step (1), to obtain hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, which was recorded as S6.

[0101] (ii) Loading active metals:

[0102] Take 100 grams of H-type Silicalite-1@ZSM-5 core-shell molecular sieve S6, impregnate it with 500 ml of ferric chloride aqueous solution with a concentration of 0.01 g / ml and a pH value of 8.5 at 80°C for 2 hours, dry the impregnated solid at 100°C for 4 hours, and then transfer it to a muffle furnace for a first calcination at 550°C for 6 hours to obtain hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve S6' loaded with active metals.

[0103] (III) Molding:

[0104] Take 60g S6' and 40g pseudo-boehmite powder (produced by Sasol, Germany, with an alumina content of 75% by mass, the same below) and mix them evenly, add 50g of a 1.0% by mass nitric acid aqueous solution, knead and shape them, and extrude them into particles with a diameter of 2mm and a length of 2-3mm using an extruder. Perform a second drying at 100°C in an oven for 5h, and then transfer them to a muffle furnace at 650°C for a second calcination for 5h to obtain the catalyst C6.

[0105] Table 1 shows the characterization results of the structural properties of S6, S6' and C6, and Table 2 shows the composition of catalyst C6.

[0106] Example 7

[0107] (I) Preparation of hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve:

[0108] Silicalite-1@ZSM-5 core-shell molecular sieve was prepared according to the method of Example 1, except that the molar ratio of silica sol (in terms of SiO2): sodium metaaluminate (in terms of Al2O3) in step (2) was 200, and the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve was obtained, which was denoted as S7.

[0109] (ii) Loading active metals:

[0110] 100 g of H-type Silicalite-1@ZSM-5 core-shell molecular sieve S7 was impregnated with 500 ml of a hexahydrated cobalt nitrate aqueous solution with a concentration of 0.01 g / ml and a pH value of 8.5 at 80°C for 2 hours. The impregnated solid was first dried at 120°C for 4 hours, and then transferred to a muffle furnace for a first calcination at 500°C for 8 hours to obtain a hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve S7' loaded with active metals.

[0111] (III) Molding:

[0112] Take 60g S7' and 40g pseudo-boehmite powder (produced by Sasol, Germany, with an alumina content of 75% by mass, the same below) and mix them evenly, add 50g of a 1.0% by mass nitric acid aqueous solution, knead and shape them, and extrude them into particles with a diameter of 2mm and a length of 2-3mm using an extruder. Perform a second drying at 100°C in an oven for 3h, and then transfer them to a muffle furnace at 550°C for a second calcination for 6h to obtain the catalyst C7.

[0113] Table 1 shows the characterization results of the structural properties of S7, S7' and C7, and Table 2 shows the composition of catalyst C7.

[0114] Example 8

[0115] Catalyst C8 was prepared according to the method of Example 4 except that The step of loading active metals, Table 1 shows the characterization results of the structural properties of C8, and Table 2 shows the composition of catalyst C8.

[0116] Comparative Example 1

[0117] (I) Preparation of hydrogen-type ZSM-5 molecular sieve:

[0118] Under stirring conditions, sodium aluminate, silica sol, sodium chloride, sodium hydroxide, ZSM-5 seed crystals (silicon-aluminum ratio of 40) and deionized water are added to a reactor to obtain a ZSM-5 molecular sieve synthesis system, wherein the mass ratio of sodium aluminate (in terms of Al2O3): NaOH: sodium chloride: ZSM-5 seed crystals: water is 1:4.8:4.7:2.5:28, and the molar ratio of silica sol (in terms of SiO2): sodium aluminate (in terms of Al2O3) is 40. After stirring evenly, the mixture is aged at 35°C for 8 hours and then transferred to a crystallization kettle for crystallization at 150°C for 48 hours. The obtained solid is washed, dried and calcined to obtain a ZSM-5 molecular sieve with a silicon-aluminum ratio of 40. Take 100 grams of the ZSM-5 molecular sieve with a silicon-aluminum ratio of 40, perform ion exchange in 500 ml of ammonium chloride solution with a concentration of 1 mol / L, and then wash and calcine again to obtain a hydrogen-type ZSM-5 molecular sieve. Denoted as D1.

[0119] (ii) Loading active metals:

[0120] Take 100 grams of H-type ZSM-5 molecular sieve D1, impregnate it with 300 ml of cobalt nitrate hexahydrate aqueous solution with a concentration of 0.01 g / ml and a pH value of 8.5 at 80°C for 2 hours, dry the impregnated solid at 120°C for 4 hours, and then transfer it to a muffle furnace and calcine it at 550°C for 6 hours to obtain hydrogen-type ZSM-5 molecular sieve D1' loaded with active metals.

[0121] (III) Molding:

[0122] Take 62g D1' and 38g pseudo-boehmite powder (produced by Sasol, Germany, with an alumina content of 75% by mass, the same below) and mix them evenly, add 50g of a 1.0% by mass nitric acid aqueous solution, knead and shape them, and extrude them into particles with a diameter of 2mm and a length of 2-3mm using an extruder. After drying in an oven at 100°C for 3h, transfer them to a muffle furnace at 550°C and calcine them for 6h to obtain the catalyst DC1.

[0123] Table 1 shows the characterization results of the structural properties of D1, D1' and DC1, and Table 2 shows the composition of catalyst DC1.

[0124] Comparative Example 2

[0125] (I) Preparation of hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve:

[0126] The hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve D2 was prepared according to the method of Example 4.

[0127] (ii) Molding:

[0128] Take 65g D3 and 35g pseudo-boehmite powder (produced by Sasol, Germany, with an alumina content of 75% by mass, the same below) and mix them evenly, add 50g of a 1.0% by mass nitric acid aqueous solution, knead and shape them, and extrude them into particles with a diameter of 2mm and a length of 2-3mm using an extruder. Dry them in an oven at 100°C for 6h, and then transfer them to a muffle furnace at 650°C and calcine them for 5h to obtain the catalyst intermediate DC2'.

[0129] (III) Loading active metals:

[0130] Take 100 grams of the catalyst intermediate DC2' and impregnate it with 500 ml of a hexahydrate cobalt nitrate aqueous solution with a concentration of 0.01 g / ml and a pH value of 8.5 at 80°C for 2 hours. The impregnated solid is dried at 100°C for 4 hours. After drying, it is transferred to a muffle furnace at 550°C and calcined for 6 hours to obtain catalyst DC2. Table 2 shows the composition of catalyst DC2.

[0131] As shown in Table 1 and Table 2, compared with the ZSM-5 molecular sieve Compared with the preparations described in Examples 1-2 and 4-7 of the present invention, Silicalite-1@ZSM-5 core-shell molecular sieve After loading the metal, the total specific surface area and micropore specific surface area decreased slightly, indicating that the introduction of the non-precious metal active component did not block the pores of the carrier, and the high dispersion did not significantly reduce the specific surface area of ​​the carrier. Compared with the comparative example 2, which was formed first and then loaded with active metals, the catalyst prepared by the molecular sieve of the present invention in Example 4, which was first loaded with active metals and then formed, had a larger total specific surface area and total pore volume.

[0132] Table 1

[0133]

[0134]

[0135] Table 2

[0136]

[0137] Test Example 1

[0138] Catalysts C1-C8 and DC1-DC2 prepared in Examples 1-8 and Comparative Examples 1-2 were tested for catalytic performance.

[0139] The small fixed bed reactor was loaded with catalysts C1-C8 and DC1-DC2, respectively. n-pentane and n-hexane were introduced into the reactor as raw materials in a volume ratio of 1:1, contacted with the catalyst and reacted for 24 hours. The volume ratio of nitrogen to raw materials was 1500:1. Other reaction conditions and results are shown in Table 3.

[0140] Table 3

[0141]

[0142] Note: Dry gases include H2, CH4 and C2 hydrocarbons.

[0143] It can be seen from the data in Table 3 that, compared with the catalyst containing ZSM-5 molecular sieve provided in Comparative Example 1, the catalyst of the hydrogen-containing Silicalite-1@ZSM-5 core-shell molecular sieve provided by the present invention is used for the aromatization reaction of light hydrocarbons, which can obtain a higher yield of low-carbon alkanes and a lower dry gas yield; the amount of catalyst carbon deposition is small, indicating that the catalyst of the present invention can greatly reduce the occurrence of side reactions such as cracking. Compared with the catalyst C8 without active metal loading, the catalyst C4 of the present invention has a higher yield of low-carbon alkanes and less catalyst carbon deposition under the same reaction conditions.

[0144] Test Example 2

[0145] The catalyst C1 prepared in Example 1 was subjected to a stability test.

[0146] Test conditions: A small fixed bed reactor was loaded with the catalyst C1 prepared in Example 1, and n-pentane and n-hexane raw materials with a volume ratio of 1:1 were introduced into the reactor to contact with the catalyst C1 and react. The reaction conditions included: temperature of 400°C, pressure of 0.1 MPa, mass space velocity of 0.5 h -1 , the volume ratio of nitrogen to raw material is 1500, and the reaction results are listed in Table 4.

[0147] Table 4

[0148] Continuous reaction time, h 24 48 72 96 120 Dry gas yield, wt% 5.24 4.26 3.92 4.09 3.82 (Propane + butane) yield, wt% 85.21 83.52 82.37 80.49 77.48 <![CDATA[C 5+ Yield, wt%]]> 9.53 12.21 13.71 15.40 18.69 Aromatic yield, wt% 1.23 5.52 7.41 8.87 11.04

[0149] Note: Dry gases include H2, CH4 and C2 hydrocarbons.

[0150] It can be seen from the data in Table 4 that with the extension of the reaction time, the (propane + butane) yield decreases from 85.21wt% when the continuous reaction is 24h to 77.48wt% when the continuous reaction is 120h, the average (propane + butane) yield is greater than 80wt%, the dry gas yield decreases from 5.24wt% when the continuous reaction is 24h to 3.82wt% when the continuous reaction is 120h; the aromatics yield increases from 1.02wt% when the continuous reaction is 24h to 11.04wt% when the continuous reaction is 120h. The catalyst provided by the present invention has good reaction activity, low-carbon alkane yield, and low dry gas yield.

[0151] Test Example 3

[0152] The catalyst C1 prepared in Example 1 was subjected to a regeneration test.

[0153] Test conditions: a small fixed bed reactor is loaded with the catalyst C1 prepared in Example 1, and n-pentane and n-hexane in a volume ratio of 1:1 are introduced into the reactor as raw materials, contacted with the catalyst C1 and reacted. The reaction conditions include: temperature 400°C, pressure 0.1 MPa, mass space velocity 0.5 h -1 , time is 120h, the volume ratio of nitrogen to raw material is 1500, and the catalyst C1 which has been reacted continuously for 120h is regenerated as a deactivated catalyst.

[0154] Regeneration method: an air-nitrogen mixed gas with an oxygen content of 20 volume % was introduced into the reactor for regeneration. The regeneration conditions were as follows: temperature of 500°C, time of 8 h, pressure of 0.1 MPa, gas / agent volume ratio of 20:1, and a regenerated catalyst was obtained. The regenerated catalyst was reused in the reaction. The reaction conditions were the same as the test conditions, and the reaction time was 120 h. The reaction results are listed in Table 5.

[0155] Table 5

[0156] Catalyst regeneration times 0 1 Dry gas yield, wt% 3.82 3.16 (Propane + butane) yield, wt% 77.48 75.44 <![CDATA[C 5+ Yield, wt%]]> 18.69 21.39 Aromatic yield, wt% 11.04 11.08

[0157] Note: Dry gases include H2, CH4 and C2 hydrocarbons.

[0158] It can be seen from the data in Table 5 that after the catalyst C1 provided in Example 1 is regenerated, the catalytic activity is very close to the activity before regeneration, indicating that the catalyst provided by the present invention has good regeneration performance.

[0159] Test Example 4

[0160] The catalyst C1 prepared in Example 1 was loaded into a small fixed bed reactor, and the reformed top oil raw material was introduced into the reactor. The raw material composition is shown in Table 6, and the catalyst C1 was contacted and reacted. The reaction conditions included: temperature of 400° C., pressure of 0.1 MPa, mass space velocity of 0.5 h -1, time is 120h, volume ratio of nitrogen to raw material is 1500, and the results of reaction for 24h are shown in Table 7.

[0161] Table 6

[0162]

[0163]

[0164] Note: ≤C4—alkanes with carbon numbers less than or equal to 4, i-C5—isopentane, n-C5—normal pentane, N-C5—cyclopentane, i-C6—isoalkanes with carbon numbers of 6, n-C6—normal hexane, N-C6—cyclohexane, B—benzene, >C7—alkanes with carbon numbers greater than 7.

[0165] Table 7

[0166] Dry gas yield, wt% (Propane + butane) yield, wt% <![CDATA[C 5+ Yield, wt%]]> Aromatic yield, wt% C1 4.96 68.92 26.12 8.62

[0167] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A light hydrocarbon aromatization catalyst for producing more low-carbon alkanes, comprising a hydrogenated Silicalite-1@ZSM-5 core-shell molecular sieve, an active metal and / or a binder, wherein the hydrogenated Silicalite-1@ZSM-5 core-shell molecular sieve has a Silicalite-1 molecular sieve as a core layer and a ZSM-5 molecular sieve as a shell layer, and has a particle size of 90 to 140 nm.

2. The catalyst according to claim 1, characterized in that The active metal is a Group VIII metal, preferably one of cobalt, nickel and iron; the binder is silicon oxide or aluminum oxide.

3. The catalyst according to claim 1, characterized in that The content of the active metal is 0 to 10.0% by mass, preferably 0 to 6.0% by mass, calculated based on the mass of the molecular sieve.

4. The catalyst according to claim 1, characterized in that The content of the binder is 0-45% by mass, calculated based on the total mass of the hydrogenated Silicalite-1@ZSM-5 core-shell molecular sieve and the binder.

5. The catalyst according to claim 1, characterized in that The hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve has a particle size of 100 to 130 nm; the particle size of the Silicalite-1 molecular sieve is 40 to 80 nm, preferably 50 to 70 nm; the shell thickness of the ZSM-5 is 30 to 70 nm, preferably 45 to 60 nm; the silicon-aluminum ratio of the ZSM-5 molecular sieve is 20 to 200, preferably 40 to 80; the total specific surface area of ​​the Silicalite-1@ZSM-5 core-shell molecular sieve is 300 to 470 m 2 / g, preferably 420-450m 2 / g, micropore specific surface area is 260~390m 2 / g, preferably 350 to 380 m 2 / g, total pore volume is 0.20~0.60cm 3 / g, preferably 0.30 to 0.55 cm 3 / g, micropore volume is 0.10~0.30cm 3 / g, preferably 0.16 to 0.28 cm 3 / g.

6. The catalyst according to claim 1, characterized in that The total specific surface area of ​​the catalyst is 200 to 420 m 2 / g, preferably 240-280m 2 / g, total pore volume is 0.30~0.70cm 3 / g, preferably 0.40-0.50cm 3 / g.

7. The catalyst according to claim 1, characterized in that When the catalyst does not contain a binder, the micropore specific surface area of ​​the catalyst is 330 to 370 m 2 / g, micropore volume is 0.10~0.20cm 3 / g.

8. The catalyst according to claim 1, characterized in that The hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve is obtained by a preparation process comprising the following steps: (1) mixing a template, a first silicon source and water to obtain a core-shell molecular sieve synthesis system, and performing aging I and crystallization I to obtain an intermediate product; (2) The intermediate product obtained in step (1), an aluminum source, a second silicon source, an alkali source, an anion-cation balance agent and water are mixed to obtain a shell molecular sieve synthesis system, and after aging II and crystallization II, the obtained solid is washed, dried and then calcined to obtain the Sililcalite-1@ZSM-5 core-shell molecular sieve; (3) The Sililcalite-1@ZSM-5 core-shell molecular sieve obtained in step (2) is subjected to ion exchange in a solution containing ammonium ions, and is washed, dried and calcined again to obtain the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve.

9. The catalyst according to claim 8, characterized in that A hydrolysis promoter is added to the core layer molecular sieve synthesis system in step (1), wherein the hydrolysis promoter is an alcohol and / or a weak base.

10. The catalyst according to claim 8, characterized in that The hydrolysis accelerator is at least one of ethylene glycol, ethanol, methanol and ammonia water.

11. The catalyst according to claim 8, characterized in that The anion-cation balance agent is one of a strong acid-weak base salt, a strong base-weak acid salt, a strong acid-strong base salt or a weak acid-weak base salt.

12. The catalyst according to claim 8, characterized in that The anion-cation balance agent is at least one of sodium acetate, sodium chloride, ammonium acetate and ammonium chloride.

13. The catalyst according to claim 8, characterized in that The first silicon source and the second silicon source are independently selected from at least one of tetraethyl silicate, silica sol, water glass, white carbon black, and silica gel powder; the aluminum source is at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, and aluminum chloride; the alkali source is at least one of sodium hydroxide, potassium hydroxide, and ammonia water; the template is at least one of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, n-butylamine, tetrapropylammonium bromide, and 1,6-hexanediamine.

14. The catalyst according to claim 8, characterized in that The step (1) includes a step of recovering the template by distillation or centrifugation after crystallization I.

15. The catalyst according to claim 14, characterized in that The temperature of the distillation recovery template agent is 60-120° C., preferably 80-100° C., and the distillation time is 0.5-6 hours, preferably 2-4 hours.

16. The catalyst according to claim 8, characterized in that The mass ratio of the first silicon source to the template agent is 0.1-5, and the mass ratio of the first silicon source to water is 1-10.

17. The catalyst according to claim 16, characterized in that The mass ratio of the first silicon source, calculated as SiO2, to the hydrolysis accelerator is 1 to 5.

18. The catalyst according to claim 8, characterized in that The second silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the molar ratio of the second silicon source to the aluminum source is 20-200.

19. The catalyst according to claim 8, characterized in that The aluminum source is calculated as Al2O3, the alkali source is calculated as NaOH, and the mass ratio of intermediate product: aluminum source: alkali source: anion and cation balance agent: water is (50-300): 1: (1-10): (1-30): (50-200).

20. The catalyst according to claim 8, characterized in that The aging I has a temperature of 10-50°C, preferably 25-35°C, and a time of 0.5-12h, preferably 4-6h; the crystallization I has a temperature of 80-250°C, preferably 100-150°C, and a time of 18-72h, preferably 24-48h; the aging II has a temperature of 10-50°C, preferably 25-35°C, and a time of 0.5-12h, preferably 4-6h; the crystallization II has a temperature of 80-250°C, preferably 150-200°C, and a time of 18-72h, preferably 24-48h.

21. The method for preparing the catalyst according to claim 1, characterized in that: When the catalyst comprises hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve and active metal, its preparation method comprises: impregnating the hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve with a solution of a compound containing active metal under alkaline conditions, and then performing a first drying and a first calcination step ST1; when the catalyst comprises hydrogen-type Silicalite-1@ZSM-5 core-shell molecular sieve, active metal and a binder, further mixing the product obtained in the step ST1, a binder precursor and a peptizing agent to form, and then performing a second drying and a second calcination step ST2.

22. The method according to claim 21, characterized in that In the impregnation, the amount of the hydrogenated Silicalite-1@ZSM-5 core-shell molecular sieve and the solution containing the active metal compound is 0.1-10 g / ml; the alkaline condition is pH 8-12, preferably pH 8-10; the impregnation temperature is 30-100° C., preferably 45-75° C.

23. The method according to claim 22, characterized in that The active metal-containing compound is a soluble Group VIII metal salt; the impregnation method is excess impregnation, equal volume impregnation, precipitation impregnation or multiple impregnation methods, and the preferred method is precipitation impregnation.

24. The method according to claim 23, characterized in that The soluble Group VIII metal salt is one of a soluble cobalt salt, a soluble nickel salt and a soluble iron salt.

25. The method according to claim 24, characterized in that The soluble cobalt salt is selected from cobalt nitrate hexahydrate and cobalt chloride, the soluble nickel salt is selected from nickel nitrate hexahydrate, nickel chloride and nickel sulfate, and the soluble iron salt is selected from ferric chloride, ferric nitrate and ferric sulfate.

26. The method according to claim 21, characterized in that The peptizing agent is nitric acid and / or an organic acid, the acid concentration in the peptizing agent is 0.1-5wt%, preferably 0.5-2wt%, and the amount of the peptizing agent relative to the product obtained in step ST1 is 0.01-0.1ml / g; the binder precursor is pseudo-boehmite powder or silica gel powder; the first drying and second drying temperatures are independently 50-200°C, preferably 80-120°C, the first drying and second drying times are independently 2-8h, preferably 4-6h; the first calcination and second calcination temperatures are independently 400-700°C, preferably 450-600°C, the first calcination and second calcination times are independently 4-12h, preferably 6-8h.

27. A light hydrocarbon aromatization reaction method for producing more low-carbon alkanes, characterized in that: In the presence of an inert gas and under aromatization reaction conditions, a light hydrocarbon-containing feedstock is contacted with a catalyst and reacted. The catalyst is a catalyst according to any one of claims 1 to 20 or a catalyst prepared by a method according to any one of claims 21 to 26.

28. The reaction method according to claim 26, characterized in that The aromatization reaction conditions are: temperature 380-450°C, pressure 0.1-1 MPa, feed mass space velocity 0.1-5 h -1 , the volume ratio of inert gas and light hydrocarbon is 500-2000:

1.

29. The reaction method according to claim 26, characterized in that The light hydrocarbons are C5-C10 alkanes, preferably C5-C7 alkanes.

Citation Information

Patent Citations

  • Method for producing propane and gasoline from alkane

    CN110951500A

  • Catalyst for producing propane by light hydrocarbon conversion as well as preparation method and application thereof

    CN112588314A

  • Preparation method and application of catalyst for preparing propane through hydrogenation modification

    CN113385215A

  • Core-shell structure catalyst for propane aromatization as well as preparation method and application of core-shell structure catalyst

    CN115400785A

  • Light hydrocarbon catalytic cracking catalyst as well as preparation method and application thereof

    CN115518678A

Cited By

  • Core-shell type MFI molecular sieve as well as preparation method and application thereof

    CN122006797A

  • Selective hydrogen burning catalytic material as well as preparation method and application thereof

    CN122399886A

  • A selective hydrogen calcination catalyst, its preparation method and application

    CN122399886B